1986
DOI: 10.1007/bf00229128
|View full text |Cite
|
Sign up to set email alerts
|

Static vergence and accommodation: population norms and orthoptics effects

Abstract: The steady-state characteristics of the accommodation and vergence systems can be described by a model with six major oculomotor parameters. These include the system biases (tonic vergence and accommodation) and forward-loop gains (vergence and accommodative gains), as well as the interactive system gains (AC/A and CA/C ratios). We investigated these parameters in two populations: (1) 22 visually-normal asymptomatic individuals, and (2) 21 visually-abnormal symptomatic individuals before and after conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…17 The near point of convergence (NPC) measures the closest point to which one can maintain convergence while focusing on an object before diplopia occurs. 18 Previously, we reported that frontal soccer headings immediately increased (worsened) NPC compared with baseline, with NPC impairment persisting for 24 hours after heading. 19 The near point of convergence immediately after and 24 hours after heading were higher than in control individuals.…”
Section: Invited Commentarymentioning
confidence: 97%
“…17 The near point of convergence (NPC) measures the closest point to which one can maintain convergence while focusing on an object before diplopia occurs. 18 Previously, we reported that frontal soccer headings immediately increased (worsened) NPC compared with baseline, with NPC impairment persisting for 24 hours after heading. 19 The near point of convergence immediately after and 24 hours after heading were higher than in control individuals.…”
Section: Invited Commentarymentioning
confidence: 97%
“…From the current models, this improved ability of the vergence system to adapt following fusional vergence training is predicted to modify the cross-link ratios. Although a few studies showed the possibility of the change in the ratios (Flom, 1959;Manas, 1958;Hung et al, 1986), a recent study did not show a significant alteration with training (Brautaset & Jennings., 2006).…”
Section: Normalizing Vergence Adaptation With Positive Fusional Vergementioning
confidence: 99%
“…1 MA represent the reciprocal of the distance in meters to which the eyes are converged (Fincham & Walton, 1957). Some of these studies are confounded by the effect of age, which causes a decrease in accommodation function, leading to an increase in the response AC/A Ciuffreda, Rosenfield, & Chen, 1997;Fincham & Walton, 1957;Hung, Cuiffreda, & Semmlow, 1986;Rosenfield, Ciuffreda, & Chen, 1995) and decrease in the response CA/C ratio Rosenfield, Ciuffreda, & Chen, 1995;Wick & Currie, 1991). In addition, some studies have small subject numbers (Alpern, 1962;Morgan, 1968;Ogle, Martens, & Dyer, 1967;, and none have quantified the stimulus and response ratios for both AC/A and CA/C within the same population.…”
Section: Introductionmentioning
confidence: 96%
“…The accommodation loop was opened using a difference of Gaussian target and the authors suggested this method could be employed to measure the stimulus CA/C in clinical practice . Other studies have examined only the response CA/C ratio Hung, Cuiffreda, & Semmlow, 1986;Rosenfield, Ciuffreda, & Chen, 1995) and further work is required to establish the characteristics of the relationship between stimulus and response CA/C ratio in a larger sample.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation